Mitigation Scenario for Reducing Greenhouse Gas Emission from Rice Field by Water Management and Rice Cultivars - Ali Pramono; Terry Ayu Adriany; Helena Lina Susilawati (JOURNAL OF TROPICAL SOILS, 2020)
Rice production is a significant anthropogenic source of methane (CH4) and nitrous oxide (N2O), two important greenhouse gases (GHGs). Several strategies for reducing GHGs emissions from paddy fields are water management and the use of low emission rice cultivars. The purpose of this study was to determine the effects of water management and rice cultivars on the grain yield and greenhouse gas (GHG) emissions. The research was conducted at the Indonesian Agricultural Environment Research Institute (IAERI), Pati District, Central Java Province during the dry season 2017 (March-June 2017). The study used a factorial randomized block design with the first factor were water managements: A1 = continuous flooding at 5 cm height and A2 = alternate wetting and drying/AWD), and the second factor were rice cultivars: V1 = Ciherang, V2 = Inpari 32, V3 = Mekongga with three replications. All treatments received an equal amount of farmyard manure and inorganic fertilizers. GHG measurements were done by using a closed chamber method. The results of this study indicated that the combination of AWD treatment with Ciherang, Inpari 32, and Mekongga rice cultivars significantly reduced CH4 emissions by 23%, 46%, and 6%, respectively. The Inpari 32 rice variety produced the highest grain yield compared to others, but there were no significant differences in grain yield between all of the treatments. Therefore, AWD technique in combination with Inpari 32 rice cultivar could be a potential option for maintaining the yield-scaled global warming potential of rice production at a lower level, without reducing grain yield.